Advanced writing with English in use (CAE) - Cory, Hugh (Oxford Univ, 1997)
The book features comprehensive study of writing techniques, from essential sub-skills to full-scale exam tasks; innovative combining of English in Use and Writing work: grammar is studied as a route to better writing, writing is used to contextualize grammar; advice, training and practice, providing full exam preparation;...